The role of the emergency nurse within the prehospital environment and the emergency room - Gassiep, Jasmin (My University, 2006)
Currently the role of the Emergency Nurse in South Africa is not clearly defined. Nursing legislation does not effectively guide these nurses to enable them to cope with the high expectations and increasing demands for emergency care. Nor does it provide adequate legislative protection especially with regard to the responsibilities within the prehospital environment. This creates role confusion and conflict, which has a negative impact on the patient who requires emergency care, the advanced nurse practitioner and the emergency team. . The purpose of this research was to explore and describe the role of the South African emergency nurse in the prehospital environment and the emergency room and to formulate an instrument that can be used for policy formation, education, training and evaluation. The purpose was addressed though an action research process where data was collected in four phases that included both qualitative and quantitative methods. The process involved a group of experts who utilized their expert knowledge, skills and attitudes to explore and describe the phenomena being researched. They confirmed that the environment in which emergency nurses worked included the pre-hospital environment and emergency room. The data/roles identified and analysed were weighted to provide a weighting scale by means of a methodology referred to as “ Modelling of Human Judgement”. A competency rating was done to provide a three-point competency rating. The data/roles obtained was developed into a questionnaire and sent to the rest of the emergency nurse population for validation and verification. After validation and verification the information gathered was reduced, organized and with the assistance of a statistician (throughout all the phases) the data was analysed and an instrument developed for use as a policy framework for e.g. a scope of practice and unit standards. The instrument was quantified for educational and evaluation purposes. The instruments can be used to develop high levels of competency to encourage interdependent and autonomous decision-making, which is based on the knowledge of role expectations and sound professional decision making, which in turn is supported by appropriate legislation.
Faculty of Health Sciences School of Therapelitics 0009448d jasmin@tiscali.co.za
Keywords: Nurse; Role; Prehospital; Trauma